MANAGEMENT MODEL OF BUSINESS DEVELOPMENT BASED ON CLUSTER CONSTRAINS - Shkoda, Mariana (Journal of Strategic Economic Research, 2022)
The main goal of this work is to investigate the management model of business development based on cluster constrains. The article uses general scientific research methods, in particular, empirical methods to describe the basic approaches to modeling business development management in cluster conditions, theoretical methods, in particular, the classification of the concept of business development management on the basis of cluster partnership, etc. The article explores approaches to modeling business development management based on cluster partnerships. Four basic approaches are distinguished: structural modeling, game approach, neural network approach and statistical approach. It is emphasized that the activation of business development based on cluster partnership increases the competitiveness of all economic agents of the network. Since it is practically impossible to make optimal decisions due to the diversity of partner participants, a partnership method is proposed as an alternative, which allows reaching local compromises and making “quasi-optimal management decisions”. It is emphasized that in the process of making optimal decisions on business management based on cluster partnership, it is advisable to use holistic management based on the perception of cluster partnership as a whole. It is noted that in order to holistically, holistically consider business management based on cluster partnership, it is necessary to take into account intercorrelated aspects such as four sectors (individual internal, individual external, collective internal and collective external), development lines (vertical and horizontal, growth and decline, internal and external); levels of business development based on cluster partnerships that meet the previous aspects; choice of management activities depending on the situation, experience and knowledge; definition of management for each of the participants in the cluster partnership.